Quick Response Indonesian Standard (QRIS): Does Government Support Contribute to Cashless Payment System Long-term Adoption? - Ajeng Awliya Puspitasari; Imam Salehudin (Journal of Marketing Innovation (JMI), 2022)
The Indonesian payment system industry and regulator have created a standard QR Code in Indonesia that applies to all payment system operators, known as the Quick Response Indonesian Standard (QRIS). QRIS payments are designed to make transactions easier, faster, and safer. The goal of this study was to look at the relationship between effort expectancy, social influence, innovativeness, perceived usefulness, government support, and behavioral intention to use QRIS in the future. This study included 275 Indonesian respondents who had made payments through QRIS. The findings indicate that government support has a positive and significant relationship with behavioral intention to continue using QRIS, both directly and through the mediation of trust and perceived usefulness. Furthermore, effort expectancy, social influence, innovativeness, perceived usefulness, and trust have a direct impact on behavioral intention. As the implication, QRIS implementation must not rely solely on government approval but must actively leverage that approval to build positive user experiences and trust, which drives to the long-term adoption intention.